THE TRANSLATION OF CIVIL AVIATION SAFETY REGULATION PART 170 AIR TRAFFIC RULES INTO INDONESIAN - Sylvia Tiara; Hutabarat Tommy Liber; Saragih Azhari Nisa; Sinambela Marzuki (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
The background of this research was based on the continued development of international aviation in the world which was a challenge for the translator to find an equivalent sentence. The purpose of this thesis was to find the equivalence type used in translating the source language to the target language and find the dominant equivalence type used. For solving this problem, the writer used Nida and Taber theory that divided equivalence types into two types, namely formal equivalence or formal correspondence and dynamic equivalence. The method used was descriptive qualitative method. The data was obtained through systematic sampling method. Based on the analysis, the equivalence types of 53 of 66 samples (80%) were translated by using formal correspondence; 12 of 66 samples were translated using dynamic equivalence (18%) and only one sample (2%) did not neither involve in formal correspondence nor dynamic equivalence because SL text did not have translation in TL (reserved). The most dominant equivalence type used in the translation was formal correspondence.